Changes in olive oil volatile organic compounds induced by water status and light environment in canopies of Olea europaea L. trees. (21st November 2014) - Benelli, Giovanni; Caruso, Giovanni; Giunti, Giulia; Cuzzola, Angela; Saba, Alessandro; Raffaelli, Andrea; Gucci, Riccardo
Abstract BACKGROUND Light and water are major factors in fruit development and quality. In this study, the effect of water and light in Olea europaea trees on volatile organic compounds (VOCs) in olive oil was studied over 2 years. Mature fruits were harvested from three zones of the canopy with different light exposure (64%, 42% and 30% of incident light) of trees subjected to full, deficit or complementary irrigation. VOCs were determined by SPME GC‐MS and analysed by principal component analysis followed by discriminant analysis to partition treatment effects. RESULTS Fruit fresh weight and mesocarp oil content decreased in zones where intercepted light was less. Low light levels significantly slowed down fruit maturation, whereas conditions of water deficit accelerated the maturation process. The presence of cyclosativene and α‐muurulene was associated with water deficit, nonanal, valencene with full irrigation; α‐muurulene, (E)‐2‐hexanal were related to low light conditions, while trans‐β‐ocimene, α‐copaene, (Z)‐2‐penten‐1‐ol, hexanal and nonanal to well exposed zones. The year strongly affected the VOC profile of olive oil. CONCLUSION This is the first report on qualitative changes in VOCs induced by light environment and/or water status. This information is valuable to better understand the role of environmental factors on the sensory quality of virgin olive oil. © 2014 Society of Chemical Industry